Effect of post-exercise hydrotherapy water temperature on subsequent exhaustive running performance in normothermic conditions - Dunne, A.; Crampton, D.; Egaña, M. (Journal of Science and Medicine in Sport, 2013)
Objective: Despite the widespread use of cold water immersion (CWI) in normothermic conditions, little data is available on its effect on subsequent endurance performance. This study examined the effect of CWI as a recovery strategy on subsequent running performance in normothermic ambient conditions (?22 °C). Design: Nine endurance-trained men completed two submaximal exhaustive running bouts on three separate occasions. The running bouts (Ex1 and Ex2) were separated by 15 min of un-immersed seated rest (CON), hip-level CWI at 8 °C (CWI-8) or hip-level CWI at 15 °C (CWI-15). Methods: Intestinal temperature, blood lactate and heart rate were recorded throughout and , running economy and exercise times were recorded during the running sessions. Results: Running time to failure (min) during Ex2 was significantly (p < 0.05, ES = 0.7) longer following CWI-8 (27.7 ± 6.3) than CON (23.3 ± 5) but not different between CWI-15 (26.3 ± 3.4) and CON (p = 0.06, ES = 0.7) or CWI-8 and CWI-15 (p = 0.4, ES = 0.2). Qualitative analyses showed a 95% and 89% likely beneficial effect of CWI-8 and CWI-15 during Ex2 compared with CON, respectively. Time to failure during Ex2 was significantly shorter than Ex1 only during the CON condition. Intestinal temperature and HR were significantly lower for most of Ex2 during CWI-8 and CWI-15 compared with CON but they were similar at failure for the three conditions. Blood lactate, running economy and were not altered by CWI. Conclusions: These data indicate that a 15 min period of cold water immersion applied between repeated exhaustive exercise bouts significantly reduces intestinal temperature and enhances post-immersion running performance in normothermic conditions.